2021
DOI: 10.3389/fmed.2020.603961
|View full text |Cite
|
Sign up to set email alerts
|

Functional Exhaustion of Type I and II Interferons Production in Severe COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged in Wuhan in December 2019 and has since spread across the world. Even though the majority of patients remain completely asymptomatic, some develop severe systemic complications. In this prospective study we compared the immunological profile of 101 COVID-19 patients with either mild, moderate or severe form of the disease according to the WHO classification, as well as of 50 healthy subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 67 publications
2
42
0
1
Order By: Relevance
“…These facts can support the relation with proteinuria and cytokine storm in SARS-CoV-2 infection. As described previously, inflammatory cytokines IL1β, IL6, IL8, and TNFα increased in the plasma of moderate and severe COVID-19 patients (Ruetsch et al, 2021). Cytokine storm may contribute to COVID-19 AKI by cooperating with renal resident cells and promoting tubular and endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…These facts can support the relation with proteinuria and cytokine storm in SARS-CoV-2 infection. As described previously, inflammatory cytokines IL1β, IL6, IL8, and TNFα increased in the plasma of moderate and severe COVID-19 patients (Ruetsch et al, 2021). Cytokine storm may contribute to COVID-19 AKI by cooperating with renal resident cells and promoting tubular and endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 63%
“…Cytokine storm may contribute to COVID-19 AKI by cooperating with renal resident cells and promoting tubular and endothelial dysfunction. Previous studies described a relevant role for IL6 (Ruetsch et al, 2021). Interleukin-6 can lead renal endothelial cells to produce proinflammatory cytokines and chemokines, and can induce kidney vascular permeability, acting in microcirculatory dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ali A Ghweil and his colleagues reported that reduced leucocytes count was more likely to appear in patients with severe COVID-19 (30). Functional exhaustion of both innate and adaptive immune response was positively related to the severity of COVID-19 (31). The World Health Organization (WHO) has published guidance recommending no corticosteroids for those with non-severe COVID-19 (32), which seemed to prove our speculation to some extent.…”
Section: Discussionmentioning
confidence: 70%